The intersection of technology, demographics, and globalization: a case for second language acquisition via distance education - Bradbury, Boyd L.; Golikova, Anna (БНТУ, 2021)
Within the belief that migration and globalization have accelerated the need for second language acquisition (SLA), this case study examines the impact of technology on SLA with Russian-speaking students who are learning English via multiple means, including digital platforms. Through the utilization of the American Council on the Teaching of Foreign Languages (ACTFL) standards, the Common European Framework for Language Competence (CEFR) English proficiency scales, surveys, and participant observation, the effectiveness of technology-related approaches, such as prepared lessons, a learner management system, and virtual conversations between a native-English speaker and second language learners facilitated by bilingual (Russian/English) Belarusian instructors, researchers evaluated the impact of various aspects of SLA via technology on English Learners who reside in Belarus is under evaluation. This case study involved eight English learners between the autumn of 2018 and the spring of 2021.